L-WRN conditioned medium for gastrointestinal epithelial stem cell culture shows replicable batch-to-batch activity levels across multiple research teams - VanDussen, Kelli L. (Stem Cell Res, 2019)
Conditioned medium (CM) derived from engineered cells often facilitates the cost-effective culture of a variety of stem cells. Growing emphasis on the importance of rigor and reproducibility in lab-based science requires development of best practices approaches, including quality control procedures for the assessment of CM batches to ensure reliable interpretation and reproducibility. Here, we tested activity level variations of L-WRN CM, which is produced from an L cell line engineered to secrete Wnt3a, R spondin 3, and Noggin into a single CM that is widely used for gastrointestinal stem cell culture. We assessed 14 independent batches of L-WRN CM, produced by 5 laboratories at 3 research institutions, by multiple quantitative assays. We observed highly replicable activity levels among L-WRN CM batches prepared according to a previously published protocol. Quality control assays measuring spheroid growth or mRNA gene marker expression were best able to distinguish the quality L-WRN CM batches, whereas a Wnt reporter assay did not. Thus, we have validated that L-WRN CM activity is highly reproducible over time and between laboratories and have provided guidelines for L-WRN CM quality control testing. These validation procedures and guidelines will benefit experiment replication efforts in stem cell research.